Improved technical success and radiation safety of adrenal vein sampling using rapid, semi-quantitative point-of-care cortisol measurement. (September 2018) - Page, Michael M; Taranto, Mario; Ramsay, Duncan; van Schie, Greg; Glendenning, Paul; Gillett, Melissa J; Vasikaran, Samuel D
Objective: Primary aldosteronism is a curable cause of hypertension which can be treated surgically or medically depending on the findings of adrenal vein sampling studies. Adrenal vein sampling studies are technically demanding with a high failure rate in many centres. The use of intraprocedural cortisol measurement could improve the success rates of adrenal vein sampling but may be impracticable due to cost and effects on procedural duration. Design: Retrospective review of the results of adrenal vein sampling procedures since commencement of point-of-care cortisol measurement using a novel single-use semi-quantitative measuring device for cortisol, the adrenal vein sampling Accuracy Kit. Measurements: Success rate and complications of adrenal vein sampling procedures before and after use of the adrenal vein sampling Accuracy Kit. Routine use of the adrenal vein sampling Accuracy Kit device for intraprocedural measurement of cortisol commenced in 2016. Results: Technical success rate of adrenal vein sampling increased from 63% of 99 procedures to 90% of 48 procedures ( P = 0.0007) after implementation of the adrenal vein sampling Accuracy Kit. Failure of right adrenal vein cannulation was the main reason for an unsuccessful study. Radiation dose decreased from 34.2 Gy.cm 2 (interquartile range, 15.8–85.9) to 15.7 Gy.cm 2 (6.9–47.3) ( P = 0.009). No complications were noted, and implementation costs were minimal. Conclusions: Point-of-care cortisol measurement during adrenal vein sampling improved cannulation success rates and reduced radiation exposure. The use of the adrenal vein sampling Accuracy Kit is now standard practice at our centre.